Production of Nutri-Cereals in India: A Decomposition Analysis - Neha N Karnik (Journal of the Indian Society of Agricultural Statistics, 2024)
The study examines production of Nutri-cereals in India and the proportional contributions of area and productivity (yield) from 1950-51 to 2020-21. Production instability raises production risks and discourages farmers from investing. The Cuddy-Della Valle Index (1978) was employed in the study to address the issue of instability in Nutri-cereal production. Furthermore, it employs decomposition analysis to disassemble area, yield, and interaction effects across time. To assess decadal change, the study divided the entire era into seven sub-periods. From 1950-51 to 2020-21, the area under cultivation for jowar, bajra, ragi, and Nutri-cereals showed a negative growth rate of (-) 1.87, (-) 0.62, (-) 1.26, and (-) 1.00 percent per year, respectively. Despite this, production of all crops except jowar increased at a positive CAGR during the time. From 1950-51 to 2020-21, productivity for bajra increased at the fastest rate (2.28 percent per year), followed by ragi at 1.41 percent per year. The goal of the decomposition method is to understand the driving forces that cause changes in the impact variable. For the first three decades of jowar production, the yield effect was particularly strong. However, data over the last four decades suggests that the area impact influences jowar output. It is evidenced that yield effect has always been the driving force for producing bajra and Nutri-cereals.